ANALYTICAL HIERARCHY PROCESS AND TOPSIS APPROACH TO PERFORM SUPPLIER SELECTION IN CONSTRUCTION INDUSTRY - Filscha Nurprihatin; Riki Antonius; Glisina Dwinoor Rembulan; Rafie Djajasoepena; Eko Sulistyo (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
Suppliers play an important role as suppliers of production raw materials, making companies must choose suppliers correctly. This paper discusses the best supplier selection to avoid financial and non-financial losses This paper uses four criteria for determining the best supplier, such as price, lead time, payment terms, and quality & service. A reasonable price following initial planning is always expected by the customers. Lead time is an essential consideration to ensure on-time delivery. Failure to perform on-time delivery will direct in poor payment terms. Besides, any products that do not meet quality standards will always lead to waste. Analytical Hierarchy Process (AHP) and Technique Order Preference by Similarity to Ideal Solution (TOPSIS) are used to select and determine the best supplier for the company. Pairwise comparisons are performed by making comparisons between each criterion and the alternatives made at each level of the hierarchy in pairs to get the value of the importance of the elements in the form of a qualitative opinion. The weight values for price, lead time, payment terms, and quality and service criteria are 0.0709, 0.1409, 0.2682, and 0.5200, respectively. According to AHP, alternative weight values in each criterion are 0.3899, 0.3063, and 0.3038, namely supplier A (rank 1), supplier B (rank 2), and supplier C (rank 3), respectively. However, the results of supplier selection using the TOPSIS method are supplier B (rank 1), supplier C (rank 2), and supplier A (rank 3) with values of 518.4025, 469.2017, and 412.3928, respectively.